Employing Alternative Assessment Strategies and Their Obstacles from The Perspective of Arabic Language Teachers at the Secondary School Level - Al-Alawi, Wafa'a Hamed Muda; Haji, Khdijah Mohamad Omar (Journal of Educational and Psychological Sciences, 2023)
The study aimed to determine the extent to which Arabic language teachers at secondary school level employ alternative assessment strategies and the obstacles to their implementation from their perspective. It also indicated the impact of variables such as gender, experience, and training hours on the degree of employment of Arabic language teachers of alternative assessment strategies and the obstacles to their implementation from their perspective. A descriptive survey method was utilized to achieve the objectives of the study, and a questionnaire was designed to collect data. It was applied to a survey sample consisting of 30 male and female teachers, and after ensuring its validity and reliability, it was applied to a sample of 455 male and female teachers. After conducting appropriate statistical analyses, the researcher found the following: Arabic language teachers at the secondary school level employ a high degree of alternative assessment strategies. The top-ranked strategy was reflection-based assessment, followed by observation-based assessment, then communication-based assessment, and finally performance-based assessment. The obstacles to the employment of Arabic language teachers at the secondary school level in alternative assessment strategies were found to be significant from their perspective. The top-ranked obstacle was related to parents of students, followed by obstacles related to the educational environment, then obstacles related to educational supervision and school administration, followed by obstacles related to students, then obstacles related to teachers, and finally obstacles related to the curriculum. Based on the findings of the study, the researcher recommended providing an instruction manual for Arabic language teachers and parents that includes alternative assessment strategies. Moreover, it is crucial for educational administrations to hold intensive training courses.
Keywords: alternative assessment strategies; Arabic language teachers; secondary school level; obstacles